Feeling Happy and Sad at the Same Time? Subcultural Differences in Experiencing Mixed Emotions between Han Chinese and Mongolian Chinese - Deng, Xinmei; Ding, Xuechen; Cheng, Chen; Chou, Hiu Mei (Frontiers in Psychology, 2016)
In some occasions, people experience pleasant and unpleasant emotions at the same time in a single emotional event. Previous cross-cultural studies indicated that such mixed emotions are more prevalent in China and highly related to the attitudes toward happiness and individual’s affective motivation. However, as a multi-ethnic country, not much is known about the subcultural differences in mixed emotions in China. Thus, we examined the role that implicit attitudes toward happiness and affective motivation may play in regard of the subcultural differences in mixed emotions between Han (N = 61) and Mongolian Chinese (N = 46). Results indicated that, compared with Mongolian Chinese, Han Chinese had a stronger association between implicit contra-hedonic attitudes toward happiness and mixed emotions in a pleasant emotional event. Also, Han Chinese who reported contra-hedonic motivation in a pleasant emotional event had higher level of mixed emotions than who had hedonic motivation. No significant difference was found in the mixed emotions between Mongolian Chinese who had contra-hedonic and hedonic motivation. These results suggested that the psychological mechanisms underlying the differences in mixed emotions require a comprehensive understanding not only in cross-cultural context but also from subcultural perspective.